Selected psychosocial problems in COPD patient care - Ślusarska, Barbara; Kwaśnik, Katarzyna; Piasecka, Honorata; Nowicki, Grzegorz (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction. Chronic Obstructive Pulmonary Disease (COPD) is characterised by partially reversible limited airflow through the respiratory tract, arising from an inflammatory process that exerts a local effect on the lung tissue. It also triggers a number of extrapulmonary lesions. COPD severely influences the daily living of people experiencing this condition, reducing their overall quality of life. The aim of the study. Defining psychosocial difficulties, functional capacity and self-assesment of health among patients with COPD. Material and methods. The study covered 100 patients with spirometrically confirmed COPD, treated in hospital departments. It comprised conducting a questionnaire survey, analysing medical documentation, assessing the degree of depression (according to Beck’s Scale), and evaluating the complex activities of daily living (according to Lawton’s Scale — IADL). Results and conclusion. 66.0% of the surveyed patients were tobacco smokers with an over 10 year addiction history. The breathing difficulties assessment according to the mMRC Scale revealed that the 2 nd degree was the most frequently experienced (28% of those surveyed), followed by the 3 rd degree (26%) and then the 4 th (17%). According to 52% of the patients, the sense of helplessness in daily living was the underlying disease-related problem. Moderate depression was diagnosed in 54% of COPD patients, and severe depression in 14.0%. The occurrence and degree of depression appeared to depend on the duration of the disease treatment time (p < 0.001, r c = 0.436). As regards the assessment of daily functions according to the IADL Scale, 20% of the surveyed claimed to deal with everyday activities with minor assistance from other people, while others were self-reliant.